Calcium-based Nanosized Mixed Metal Oxides for Supercapacitor Application - Ali, Gomaa A. M.; Wahba, Osama A.G; Hassan, Ali M.; Fouad, Osama A.; K. F., Chong (Elsevier, 2015)
The nanosized mixed metal oxides (Ca3Co2O6, CaMnO3 and Ca2CuO3) have been synthesized and their electrochemical performance as super capacitor electrodes have been evaluated. All of them show good pseudo capacitance in KOH electrolyte with speciﬁc capacitance of 563, 384 and 275 Fg1 for Ca3Co2O6, CaMnO3 and Ca2CuO3, respectively. The charge kinetics of Ca3Co2O6 is further evaluated by electrochemical impedance spectroscopy and the results show the low resistivity of Ca3Co2O6 and its charge kinetic shows little variation after long continuous cycling. The present study signiﬁes the successful application of nanosized mixed metal oxides as super capacitor electrode.